Efficiency of Aqua Fitness in Physical Education of Junior Schoolchildren - Zhuk, Anna; Habinets, Tamara; Жук, Ганна; Хабінець, Тамара (Східноєвропейський національний університет ім. Лесі Українки, 2012)
In the article there is studied the up-to-date system of development of programs of aqua-classes at primary schoolchildren; offered some sets of aqua fitness exercises, analyzed specificity of healthy impact of aqua exercises of different intensity onto the organism of primary schoolchildren. The aim of the investigation: to determine the efficiency of using the means of aqua fitness in process of physical education of junior schoolchildren. Research techniques: theoretical analysis and integration of data from scientific-methodological literature, anthropometric and physiological research techniques, pedagogical methods (pedagogical observation, tests, experiments), method of rapid assessment of the level of physical health of children and adolescents, methods of mathematical statistics. During the research there has been substantiated a program of classes involving the innovative aqua fitness techniques for primary schoolchildren of physical health low level. In the result of executed researches there has been revealed the more positive impact of the developed program to the level of physical preparation, morph functional status, the state of schoolchildren health in comparison with generally accepted methodology. У статті висвітлено питання, які стосуються сучасної системи побудови програм занять у воді з молодшими школярами, вивчено специфіку оздоровчого впливу вправ у воді різної переважальної спрямованості на організм дітей молодшого шкільного віку. Мета дослідження – визначити ефективність застосування засобів аквафітнесу в процесі фізичного виховання молодших школярів. Методи дослідження: теоретичний аналіз й узагальнення даних науково-методичної літератури, антропометричні, фізіологічні, педагогічні (педагогічне спостереження, тестування, експеримент), методика експрес-оцінки рівня фізичного здоров’я дітей і підлітків, методи математичної статистики. У процесі дослідження обґрунтовано програму занять із застосуванням інноваційних технологій аквафітнесу для дітей молодшого шкільного віку з різним рівнем фізичного здоров’я. Результати проведених досліджень показали більш відчутний позитивний вплив розробленої програми на рівень фізичної підготовленості, морфофункціональний статус, стан здоров’я школярів, порівняно із загальноприйнятою методикою.
Ефективність застосування аквафітнесу в процесі фізичного виховання молодших школярів
Keywords: primary schoolchildren; aqua fitness; level of physical health; programming; recreational effectiveness; діти молодшого шкільного віку; аквафітнес; рівень фізичного здоров’я; програмування; оздоровча ефективність